Adrenergic modulation of hilar neuron activity and granule cell inhibition in the guinea-pig hippocampal slice - Bijak, Maria; Misgeld, Ulrich (Neuroscience, 1995)
To study the effects of norepinephrine on synaptic inhibition in the dentate gyrus, intracellular recordings were made from hilar neurons in the guinea-pig hippocampal slice. The effects of norepinephrine on hilar neurons were compared with changes in the frequency of spontaneous inhibitory postsynaptic potentials recorded from granule cells. Hilar neurons comprised two electrophysiologically distinct groups: type I hilar neurons displayed a pronounced single spike afterhyperpolarization and little spike frequency accommodation, type II hilar neurons had small afterhyperpolarizations and pronounced spike frequency accommodation. The majority of recordings were from type I hilar neurons which are presumably inhibitory to granule cells. In most instances, effects of norepinephrine (2-10 μM) on hilar neurons could be mimicked by the β-adrenergic agonist isoproterenol (0.1-1 μM). Isoproterenol induced a slight depolarization, blocked a slow afterhyperpolarization and, in type II neurons, reduced spike frequency accommodation. These effects were associated with an increase in the spontaneous discharge rate and an enhancement of spontaneous excitatory and inhibitory postsynaptic potentials. In accordance, isoproterenol andnorepinephrine increased the frequency of inhibitory postsynaptic potentials in granule cells. In the presence of the non-N-methyl-d-aspartate receptor antagonist 6-cyano-7-nitroquinoxaline-2,3-dione and theN-methyl-d-aspartate receptor antagonist CGP 37849, isoproterenol and norepinephrine also increased the frequency of Cl−-dependent inhibitory postsynaptic potentials in granule cells. Under this experimental condition, however, norepinephrine reduced the discharge stage rate of type I hilar neurons through an effect on α-receptors. In the presence of GABAA receptor blockers, norepinephrine increased the frequency of spontaneously occurring K+-dependent inhibitory postsynaptic potentials in granule cells. Accordingly, the frequency of burst discharges in type I hilar neurons was increased. We suggest that the discrepancy in the effect of norepinephrine on the discharge rate of presumed inhibitory hilar neurons and the frequency of Cl−-dependent inhibitory postsynaptic potentials in granule cells results from a direct effect of norepinephrine on GABAergic terminals because norepinephrine also enhanced the frequency of tetrodotoxin-resistant inhibitory postsynaptic potentials in granule cells. Thus, the net effect of synaptically released norepinephrine on synaptic inhibition in the dentate gyrus will be determined by opposing actions of α- versus β-receptor stimulation at the synapse on hilar neurons.
Online 6 April 2000
Gesehen am 27.04.2021
Elektronische Reproduktion der Druck-Ausgabe